Epithelial-to-mesenchymal transition drives a pro-metastatic Golgi compaction process through scaffolding protein PAQR11 - Tan, Xiaochao; Banerjee, Priyam; Guo, Hou-Fu; Ireland, Stephen; Pankova, Daniela; Ahn, Young-ho; Nikolaidis, Irodotos Michail; Liu, Xin; Zhao, Yanbin; Xue, Yongming; Burns, Alan R.; Roybal, Jonathon; et al. (The Journal of Clinical Investigation, 2017)
Tumor cells gain metastatic capacity through a Golgi phosphoprotein 3–dependent (GOLPH3-dependent) Golgi membrane dispersal process that drives the budding and transport of secretory vesicles. Whether Golgi dispersal underlies the pro-metastatic vesicular trafficking that is associated with epithelial-to-mesenchymal transition (EMT) remains unclear. Here, we have shown that, rather than causing Golgi dispersal, EMT led to the formation of compact Golgi organelles with improved ribbon linking and cisternal stacking. Ectopic expression of the EMT-activating transcription factor ZEB1 stimulated Golgi compaction and relieved microRNA-mediated repression of the Golgi scaffolding protein PAQR11. Depletion of PAQR11 dispersed Golgi organelles and impaired anterograde vesicle transport to the plasma membrane as well as retrograde vesicle tethering to the Golgi. The N-terminal scaffolding domain of PAQR11 was associated with key regulators of Golgi compaction and vesicle transport in pull-down assays and was required to reconstitute Golgi compaction in PAQR11-deficient tumor cells. Finally, high PAQR11 levels were correlated with EMT and shorter survival in human cancers, and PAQR11 was found to be essential for tumor cell migration and metastasis in EMT-driven lung adenocarcinoma models. We conclude that EMT initiates a PAQR11-mediated Golgi compaction process that drives metastasis.